Novel perspective of 'poor sleep' in public health: a narrative review - Damien Léger; Fang Han; Makoto Uchiyama; Phyllis C Zee; Luigi Ferini-Strambi; Dalva Poyares (BMJ Publishing Group, 2024)
A high percentage of people worldwide complain of sleep disturbances; however, the vast majority do not meet the diagnostic criteria for insomnia or other classic sleep disorders. Therefore, the 'classical' concept of poor sleep remains undetected, and patients stay ignored and unidentified. Also, poor sleep has been strongly associated with increased daytime function impairment, morbidity and mortality and is considered a risk factor for developing mental disorders. Poor sleep is the individual experience of insufficient restorative sleep and/or sleep satisfaction in adults who do not fulfil the criteria for sleep disorders. This article provides a review on the impact of poor sleep on a healthy life within the multidimensional concept of sleep health, including the COVID-19-affected period. We propose a wide definition of poor sleep and the key characteristics of poor sleepers and tools for (self) detection. We discuss sleep assessment methods that combine the ability to capture the subjective perception of the sleep experience and measure objective sleep parameters. We then report selected strategies to improve sleep health, focusing on healthy sleep habits, cognitive behavioural therapy, diet, exercise, food supplements and other sleep aids. Considering the current megalopolis way of life, young people are following a 24/24 hours 7 days/week rhythm of life, with increased exposure to noise and light pollution, night-shift work, higher commute time, increased global temperature and overuse of smartphones and screens. Therefore, there is an urgent need for increasing awareness of poor sleep and stimulating educational efforts targeted at poor sleepers and primary care specialists.